2019
DOI: 10.1002/pen.25173
|View full text |Cite
|
Sign up to set email alerts
|

Controlling properties of acrylate/epoxy interpenetrating polymer networks by premature termination of radical polymerization of acrylate

Abstract: An approach is presented to control properties of sequentially synthesized acrylate/epoxy interpenetrating polymer networks (IPNs) and is used to print uniform and graded properties. These IPNs are constructed by partial formation of the acrylate network, removal of the excess components, expansion with the epoxy system, and curing. The partial crosslinking of the initial network is controlled by photo polymerization and used to manipulate the final properties. The process is used to print homogeneous and grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The formed interpenetrating network benefited from much better thermomechanical properties in comparison to pristine thiol-ene networks [249]. Several other studies have been reported on the combination of radical and cationic photopolymerization to form IPNs using sequential curing [250,251]. Konuray et al applied this concept in 3D printable resin formulations and developed resin formulations with varying epoxy and acrylate monomers in different concentrations.…”
Section: Dual Curable Network (Photothermal Sequential Curing)mentioning
confidence: 99%
“…The formed interpenetrating network benefited from much better thermomechanical properties in comparison to pristine thiol-ene networks [249]. Several other studies have been reported on the combination of radical and cationic photopolymerization to form IPNs using sequential curing [250,251]. Konuray et al applied this concept in 3D printable resin formulations and developed resin formulations with varying epoxy and acrylate monomers in different concentrations.…”
Section: Dual Curable Network (Photothermal Sequential Curing)mentioning
confidence: 99%
“…This increase in thermal stability of hybrid epoxy was linked with the increase in molar mass between crosslinks, intermolecular interactions of HTTE/epoxy and crosslinked density [ 64 ]. Similarly, acrylate based epoxy system was used to toughen the epoxy resin (ECH) by varying the toughener content and the duration of UV exposure for curing [ 65 ]. The sequential IPN approach was used to prepare the modified epoxy system, i.e., the acrylate resin was partially photo-polymerized and then swollen by the epoxy resin followed by the complete curing to make IPN ( Figure 9 a).…”
Section: Ipn Based Epoxy Systems With Thermosetting Toughenersmentioning
confidence: 99%
“…The sequential IPN approach was used to prepare the modified epoxy system, i.e., the acrylate resin was partially photo-polymerized and then swollen by the epoxy resin followed by the complete curing to make IPN ( Figure 9 a). The nano-mechanical analysis showed that the elastic modulus of modified epoxy resin decreased from 715 to 16.7 MPa by increasing both acrylate content and UV exposure during curing ( Figure 9 b) [ 65 ].…”
Section: Ipn Based Epoxy Systems With Thermosetting Toughenersmentioning
confidence: 99%